1994
DOI: 10.1093/cvr/28.3.312
|View full text |Cite
|
Sign up to set email alerts
|

Acute ischaemic preconditioning and chronic hypoxia independently increase myocardial tolerance to ischaemia

Abstract: Chronic hypoxia increased myocardial tolerance to ischaemia, and acute ischaemic preconditioning increased the tolerance further. Thus chronic hypoxia and acute ischaemic preconditioning independently activate protective mechanisms against ischaemia; the mechanisms may differ between the two types of insult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
55
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 0 publications
12
55
1
Order By: Relevance
“…However, studies on adult mammalian hearts do not support this conclusion. Both Tajima et al, (1994) and Neckár et al (2002) demonstrated that although hearts from chronically hypoxic adult rats had increased resistance to ischaemia-related damage, preconditioning conferred an increased amount of protection. Taken together, these results suggest that the relationship between inherent hypoxia tolerance and the ability to be preconditioned in lower vertebrates and neonatal/immature mammals is similar, but that these two groups differ as compared with adult mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on adult mammalian hearts do not support this conclusion. Both Tajima et al, (1994) and Neckár et al (2002) demonstrated that although hearts from chronically hypoxic adult rats had increased resistance to ischaemia-related damage, preconditioning conferred an increased amount of protection. Taken together, these results suggest that the relationship between inherent hypoxia tolerance and the ability to be preconditioned in lower vertebrates and neonatal/immature mammals is similar, but that these two groups differ as compared with adult mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Baker et al (1999) showed that hearts from 7-10-day-old rabbits that were reared in a hypoxic environment (12% oxygen) developed a degree of myocardial ischaemia-tolerance (60% recovery of contractile function following 40·min of ischaemia), and no longer experienced increased functional recovery in response to preconditioning. In contrast, both Tajima et al (1994) and Neckár et al (2002) demonstrated that although hearts from chronically hypoxic adult rats had increased resistance to ischaemia-related damage, preconditioning conferred an additional amount of protection. These results question whether long-term and short-term mechanisms of ischaemic protection in the mammalian heart share the same signal transduction pathways and end-effectors, and whether the relationship between inherent hypoxia/ischaemia tolerance and preconditioning is fundamentally different between life stages.…”
mentioning
confidence: 90%
“…For example, ischaemic preconditioning failed to improve contractile function following 40·min of global ischemia in hypoxia-tolerant neonatal rat hearts (1 or 4 days post partum), only slightly (by 7%) improved contractile function in relatively hypoxia-sensitive rat hearts tested 7 days post partum (Ostadalova et al, 1998), and Baker et al (1999) showed that hearts from 7-10 day old rats that were reared in a hypoxic environment (12% oxygen) no longer experienced increased functional recovery in response to preconditioning. In contrast, both Tajima et al (1994) and Nechár et al (2002) demonstrated that although hearts from chronically hypoxic adult rats had increased resistance to ischaemia-related damage, preconditioning conferred an additional amount of protection. Thus, to examine whether hearts from hypoxiatolerant trout can be preconditioned, we recently conducted in Fig.·4.…”
Section: Hypoxic Acclimationmentioning
confidence: 94%
“…In an isolated adult rat heart model, chronic hypoxia improved postischemic systolic function and protected against prolonged periods of ischemia (27). Although similarities of the phenomena of hypoxic and ischemic preconditioning have been found in protecting the myocardium, the additive cardioprotective effects of hypoxic and ischemic preconditioning suggest different mechanisms of protection (27).…”
mentioning
confidence: 99%